Possible Existence of Melanocytes or Melanoblasts in Human Sebaceous Glands - Jang, Yong Hyun; Kim, Sang Lim; Lee, Jin Sub; Kwon, Kun-Young; Lee, Seok-Jong; Kim, Do Won; Lee, Weon Ju (Annals of dermatology, 2014)
Melanocytes are present in both basal epidermis and hair follicles. Melanocyte stem cells have been found in hair follicle bulge. During embryogenesis, the outer cells of the bulge differentiate into the sebaceous gland (SG) and proliferate. To identify and determine the distribution and morphological characteristics of melanocytes in human SGs. A total of 171 biopsy specimens of face and scalp were studied. Of these specimens, 103 samples contained SGs. We conducted a retrospective review of slides stained with H&E, F-M, anti-S100, anti-c-kit, anti-HMB-45, anti-CD1a, anti-MITF, and anti-tyrosinase. The presence and distribution of melanocytes in human SGs was also evaluated by electron microscopy. In addition, melanocytes were isolated from SGs for primary culture. S-100-positive cells were observed mainly at the periphery of SGs in 34 of 54 specimens. We did not find F-M-positive and HMB-45-positive cells in SGs. CD1a-positve cells were identified in two specimens. We also found c-kit-, MITF-, and tyrosinase-positive cells in SGs. Electron micrograph showed the presence of melanocytes in the suprabasal portion of SGs. These melanocytes showed fewer melanin-containing granules than the melanocytes of basal epidermis. However, the individually distributed melanosomes in suprabasal melanocytes were larger than those in epidermal melanocytes. Primary culture of melanocytes derived from SGs showed morphologically homogeneous, slender cell bodies with few dendrites. Our study confirms the presence of non-melanogenic melanocytes and Langerhans cells in human SGs. In addition, the characteristics of the melanocytes in SGs were found to be different from those of the epidermal melanocytes.